T-Public / Ahmad Danial Ahmad Darimi, Nurul Nadhirah Anuar ... [et al.] - Ahmad Darimi, Ahmad Danial; Anuar, Nurul Nadhirah; W.Kamarudin, W.N.Hamizah (2017)
The apps need to be download from the play store. Users can browse through the app and designer can login and create an account to post their artworks. Users can select any artworks and print into t-shirt. There are other tool to customise user's personal touch and proceed to payment and shipping. People can directly chat with the designer to order their artworks.